Diversity, abundance and distribution of benthic macrofauna on rocky shores from North Sucre State, Venezuela - Fernández, Johanna (2014)
The rocky intertidal zone is among the most extreme physical environments on Earth. Organisms living in this area are constantly stricken by physico-chemical and biological factors. Due to the ecological importance of these areas, we studied the diversity, abundance and distribution of the rocky coastline benthic macrofauna, from the North coast of Sucre State, Venezuela. We performed bimonthly samplings from November 2008 to September 2009. The collection of biological material in the littoral zone (supra, mid and infralittoral) was done manually with a grid of 0.25m2. Organisms were preserved in 10% formalin for later identification and analysis (ecological parameters and Kruskal-Wallis test to the abundance and diversity). We found a total 19 020 organisms (86spp.), in 8 phyla, 45 families and 47 genera. Mollusks were the most abundant and diverse (58 spp.), followed by arthropods (12spp.), annelids (7spp.), echinoderms (5spp.), and the less represented cnidarians, sipunculids, nemertinids and urochordates (1sp.). The zonation found coincided with the universal scheme of zonation. The towns of Rio Boca and Rio Caribe presented the highest values of ecological parameters, and the lowest were found in Playa Grande. Statistical significant differences were found in the abundance and diversity of macrofauna among the three zones. The little information on the composition and distribution of macrobenthic rocky coastline, prevents a better comparison, however the results contribute to the knowledge of the marine biodiversity in this region.